Perspectiva da centralidade do estágio supervisionado na formação em Serviço Social: questões presentes e latentes - Honorato, Andreia Agda Silva (2016)
This thesis is to study the object Supervised Internship in Social Work - their place in the training and challenges from the understanding of 18 teachers of the course of Social Service. To enter this issue considered as present and latent, was elected a five-universe (5) Education Units that make up the South II region of micro capital of the Brazilian Education and Research Association in Social Work. The overall objective focused on conduct study on supervised training in social work directing the search for debate and analysis on the perspective of the centrality of supervised training, however, in size and in all crucial considerations that print what is and what should actually be the same in the process. However, it is a thesis that defends the debate this time because there are numerous dilemmas that engender, so an environment that fosters uncover the remaining gaps in the direction of new construction coping proposituras the perspective of possibilities. Thus, the analysis from the studies and the results of the research, pointed out the need to foster new agenda for the resumption of discussion and reflection involving all or most of the UFAS through its agents for punctuated detail in each preconization debate set in National policy training in Social Work, stage place post since the 1990s, more precisely in 1996 by the Curriculum Guidelines for Social Work and regulated in the resolution n. 533 2008 of the Federal Council of Social Service, because the understanding has been multiple and adverse, which implies distortions and breaches. It is argued that it is time to fertilize the debate as points Iamamoto (2009)